A Java based interactive learning tool for antenna array pattern multiplication - Zhang, Weijun (2011)
This report summarizes the student’s experience and knowledge gained during the commitment of the final year project, which is to develop a Java based interactive learning tool for antenna array pattern multiplication. This tool is very useful to show the antenna radiation patterns based on arbitrary orientations of dipole and array directions. In order to develop this Java tool, it is required to master the knowledge in antenna array radiation theory and to acquire high-standard proficiency in Java graphics programming and Java rich client platform development. The organization of how the project has been conducted will be presented in this report. By comparing and contrasting, a Java software platform, which is most appropriate to meet this project’s requirements, has been chosen. Mockups have been set up to display the blueprints of the user-interactive frame and graphics frames. Based on the design, a Java application program that contains five layers thirteen classes has been produced by means of NetBeans platform. With respect to the limitations that have been discovered through the acceptance testing, improvement has been implemented to promote the Java tool to a more user-friendly level. Furthermore, to generalize the Java tool for two-element antenna array pattern, another Java tool dealing with the N-element antenna array pattern has been created. The resultant graphics generated by the Java tools with various input combinations indicate the influence of respective parameters on the antenna radiation pattern.